FOREIGN PHILOLOGY IN TOURISM AND ENVIRONMENT EDUCATION - Liudmyla Knodel (Pavlo Tychyna Uman State Pedagogical University, 2013)
Стаття присвячена проблемам навчання іноземних мов фахівців на сучасному етапі в нетрадиційних сферах: туризм і охорона і захист навколишнього середовища. У статті розглядаються найвідоміші вузи світу, що готують фахівців даного профілю. Наводяться дані про спеціалізації, факультети і мовні школи. У статті показані сучасні тенденції в європейській освіті в сфері іноземних мов. Статья посвящена проблемам обучения иностранным языкам специалистов в нетрадиционных сферах на современном этапе: туризм, охрана и защита окружающей среды. В статье рассматриваются самые известные вузы мира, которые готовят специалистов данного профиля. Приводятся данные по специализациям, факультетам и языковым школам. В статье отражаются современные тенденции в европейском образовании в сфере иностранных языков. The article is devoted to the problems of foreign language teaching professionals in non-traditional spheres nowadays: tourism and environment. In the article the most famous higher schools in the world, which train specialists of such type, are viewed. Data on specializations and faculties and foreign language schools are viewed in it. Present-day tendencies in European education in the sphere of foreign languages teaching are reflected in the article.